The Effect of a Synthetic Heparan Sulfate on the Healing of Colonic Anastomoses - Malene Nerstrøm; Peter-Martin Krarup; Lars Nannestad Jorgensen; Magnus S. Ågren (Gastroenterology Research and Practice)
Background. The mimetic compound OTR4120 may replace endogenous-degraded heparan sulfates that normally maintain the bioactivity of growth factors that are important for tissue repair. Herein, we investigated the effect of OTR4120 on the healing of normal colonic anastomoses. Methods. We evaluated the following two treatment groups of male Sprague Dawley rats (220–256 g): control-treated colonic anastomoses (n=25) and OTR4120-treated colonic anastomoses (n=25). We resected 10 mm of the left colon and then applied either saline alone (control) or OTR4120 (100 μg/mL) in saline to the colonic ends before an end-to-end single-layer anastomosis was constructed and again on the anastomosis before the abdomen and skin were closed. Results. On postoperative day 3, the anastomotic breaking strengths were 1.47 ± 0.32 N (mean ± SD) in the control group and 1.52 ± 0.27 N in the OTR4120-treated animals (P=0.622). We also found that the hydroxyproline concentration (indicator of collagen) in the anastomotic wounds did not differ (P=0.571) between the two groups. Conclusions. Our data demonstrate that a single local application of OTR4120 intraoperatively did not increase the biomechanical strength of colonic anastomoses at the critical postoperative day 3 when the anastomoses are the weakest.